Decreasing incidence and mortality of lung cancer in Hungary between 2011 and 2021 revealed by robust estimates reconciling multiple data sources - Gabriella Gálffy; Géza Tamás Szabó; Lilla Tamási; Veronika Müller; Judit Moldvay; Judit Moldvay; Veronika Sárosi; Anna Kerpel-Fronius; Tamás Kardos; Edit Csada; Zsolt Pápai-Székely; Zoltán Szász; et al. (Frontiers Media S.A., 2024)
ObjectiveHungary has repeatedly been shown to have the highest cancer-related mortality and incidence in Europe. Despite lung cancer being the most abundant malignant diagnosis in Hungary, numerous concerns have been raised recently regarding the bias inherent to reported incidence estimates. Re-analysis of reimbursement claims has been suggested previously by our group as an alternative approach, offering revised figures of lung cancer incidence between 2011 and 2016. Leveraging on this methodology, we aimed at updating Hungarian lung cancer incidence estimates with an additional 5 years (2017-2021), including years affected by the COVID-19 pandemic. Additionally, we also attempted to improve the robustness of estimates by taking additional characteristics of the patient pathway into account.MethodsLung cancer patients between 2011 and 2021 were identified based on reimbursement-associated ICD-10 codes, histology codes and time patterns. Multiple query architectures were tested for sensitivity and compared to official estimates of the Hungarian National Cancer Registry (HNCR). Epidemiological trends were estimated by Poisson-regression, corrected for age and sex.ResultsA total of 89,948 lung cancer patients diagnosed in Hungary between 2011 and 2021 have been identified by our study. In 2019 alone, 7,887 patients were diagnosed according to our optimized query. ESP2013 standardized rate was estimated between 92.5/100,000 (2011) and 78.4/100,000 (2019). In 2019, standardized incidence was 106.8/100,000 for men and 59.7/100,000 for women. Up until the COVID-19 pandemic, lung cancer incidence was decreasing by 3.18% (2.1%-4.3%) yearly in men, while there was no significant decrease in women. Young age groups (40-49 and 50-59) featured the largest improvement, but women aged 60-79 are at an increasing risk for developing lung cancer. The COVID-19 pandemic resulted in a statistically significant decrease in lung cancer incidence, especially in the 50-59 age group (both sexes).ConclusionOur results show that using an optimized approach, re-analysis of reimbursement claims yields robust estimates of lung cancer incidence. According to this approach, the incidence rate of male lung cancer is declining in Hungary, in concordance with the trend observed for lung cancer mortality. Among women aged 60-79, the incidence of lung cancer has risen, requiring more attention in the near future.